Coupled fluctuations in element release during dolomite dissolution - Putnis, Christine; Ruiz-Agudo, E.; Hövelmann, J. (Mineralogical Society, 2014)
Atomic force microscopy has been used to determine more precisely the mechanism of the initial stages of dolomite dissolution. Analysis of outflow solutions initially shows fluctuations of both Ca and Mg release with concentrations of Ca >> Mg. The dolomite surface dissolves congruently in the presence of slightly acidified water as confirmed by the regular spreading of characteristic rhombohedral etch pits. Direct in situ observations show that a new phase precipitates on the dissolving surface simultaneously. As the Ca and Mg release decreases with time, the precipitated phase can be seen to spread across the dolomite surface. These observations indicate that the apparent incongruent dissolution of dolomite is a two-step process involving stoichiometric dissolution with the release of Ca, Mg and CO3 ions to solution at the mineral–fluid interface coupled with precipitation of a new Mg-carbonate phase. The coupled element release confirms the interface-coupled dissolution-precipitation mechanism.